EKSTRAKURIKULER KEAGAMAAN TERHADAP PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI KOTA MAJAPAHIT - Muh. Hambali; Eva Yulianti (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
Formal education is a conscious effort that has been carried out by managers of educational organizations. This education empties into the learning process of cognitive aspects, the ability to achieve academic achievements and tested through written examinations in school. Formal education has limitations reaching the affective and psychomotor aspects of students. These two aspects have a realm for presenting superior and high personality characters. Education should bring the character of students in accordance with the expectations of the vision and mission of the educational institution. These problems need to take steps to establish religious extracurricular activities in the form of Islamic Day and routine prayer services in schools so that they can form personalities based on religious values and norms. This study uses a qualitative research approach and the type uses case studies. This research was conducted at the Brawijaya Mojokerto Islamic Middle School which aims to determine the planning of religious extracurricular programs in schools, religious extracurricular activities in efforts to shape the religious character of students in schools, and evaluate the religious extracurricular implementation of the formation of religious character of students in schools.